2010
DOI: 10.1007/s10144-010-0229-2
|View full text |Cite
|
Sign up to set email alerts
|

A frequency distribution approach to hotspot identification

Abstract: We present a new global method for the identification of hotspots in conservation and ecology. The method is based on the identification of spatial structure properties through cumulative relative frequency distributions curves, and is tested with two case studies, the identification of fish density hotspots and terrestrial vertebrate species diversity hotspots. Results from the frequency distribution method are compared with those from standard techniques among local, partially local and global methods. Our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…1. One can easily realise that a tangent with \45°slope does not necessarily correspond to areas where the variable considered, herb species richness or bird density, respectively, is found at high densities and vice versa, as pointed out by Bartolino et al (2011). In both datasets, several points with both low and high values fulfill the 45°slope tangent rule (Fig.…”
Section: Limits To the Crfd Curve Approachmentioning
confidence: 87%
“…1. One can easily realise that a tangent with \45°slope does not necessarily correspond to areas where the variable considered, herb species richness or bird density, respectively, is found at high densities and vice versa, as pointed out by Bartolino et al (2011). In both datasets, several points with both low and high values fulfill the 45°slope tangent rule (Fig.…”
Section: Limits To the Crfd Curve Approachmentioning
confidence: 87%
“…We understand that the choice of an arbitrary threshold for the identification of biodiversity hotspots is debatable [40], but several previous analyses showed that the richest 1–10% of surface could represent a substantial proportion of terrestrial species [53,54]. …”
Section: Discussionmentioning
confidence: 99%
“…Given the relatively coarse cell size we adopted, we chose the smallest neighborhood structure possible (acting as a smoothing factor [40]), corresponding to 9 cells. Then, using the same spatial randomization approach [39] with 9,999 permutations, we tested whether local correlation between species richness in one pixel and the risk of extreme climate averaged over the 9 neighboring pixels was significantly different from what would be expected in case of spatial randomness.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Bartolino et al (2011) found that local and global methods, including CRFD curves, provided rather different results in their case study on terrestrial vertebrate species diversity where the spatial autocorrelation was rather low. We agree with Cayuela et al (2011) when they say that autocorrelation is a property of the spatial process itself.…”
mentioning
confidence: 93%